Physical activity guidelines and preschooler's obesity status - Vale, S (2013)
AIM: The benefits of promoting physical activity (PA) in counteracting the high prevalence of childhood obesity have become increasingly important in the past decade. The aim of this study was to examine the association between compliance of daily PA recommendations and the risk of being overweight or obese in preschool-aged children. METHODS: The sample comprised 607 children aged 4-6 years, recruited from kindergartens located in the metropolitan area of Porto, Portugal. Preschooler's body mass index was classified according to International Obesity Task Force. PA was assessed during 7 consecutive days by accelerometer. Children were classified as meeting or not meeting PA recommendations based on two guidelines: (i) at least 3 h per day of total PA (TPA); and (ii) at least 1 h per day of moderate to vigorous PA (MVPA). RESULTS: The prevalence of overweight and obesity was 23.5 and 10.6% in girls and 17.2 and 8.9% in boys. In all, 90.2 and 97.3% of girls met the >= 1 h MVPA and >= 3 h TPA recommendations, respectively. In all, 96.2 and 99.4% boys met the >= 1 h MVPA and >= 3 h TPA recommendations, respectively. Boys were significantly more likely to achieve the >= 1 h MVPA and >= 3 h TPA recommendations than girls (P <= 0.001). Not meeting the >= 1 h MVPA guideline was associated with obesity status (OR: 3.8; IC: 1.3-10.4), in girls, but not boys. No other statistically significant associations were found. DISCUSSION: These findings suggest that over 90% of children met the recommended guidelines. There is an association with low levels of MVPA and higher obesity status among preschool girls. Further, longitudinal studies are needed to confirm these data.